IMPROVING INDONESIAN LEARNING OUTCOMES MATERIALS OF PRINCIPLES AND SUPPORTING IDEAS THROUGH JIGSAW MODEL - Rizkiyatushobaha, Firda; Setyawan, Agung (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
The problem studied in this study is the difficulty of students in understanding the main idea material and supporting ideas, causing students' academic scores on the material to decrease. For this reason, the jigsaw type cooperative learning model is used as the solution. The purpose of this research is to improve learning outcomes of Indonesian with the main ideas and supporting ideas through the jigsaw type cooperative learning model at UPT SD Negeri 134 Gresik in the 2021/2022 academic year. The type of research used is Classroom Action Research (CAR) which uses research methods quantitative. This study consisted of two cycles consisting of four important stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. The subjects in this study were all 4th grade students of UPT SD Negeri 134 Gresik. The data collection technique used to obtain information in the research is by means of observation and tests. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle II, namely cycle I (61.53%) and cycle II (84.61%). The conclusion of this study is that learning using the jigsaw type of cooperative learning model can improve the quality of Indonesian language learning and have a positive impact on improving student learning outcomes on the main ideas and supporting ideas.